2015
DOI: 10.1590/s1415-475738320140260
|View full text |Cite
|
Sign up to set email alerts
|

High interpopulation homogeneity in Central Argentina as assessed by Ancestry Informative Markers (AIMs)

Abstract: The population of Argentina has already been studied with regard to several genetic markers, but much more data are needed for the appropriate definition of its genetic profile. This study aimed at investigating the admixture patterns and genetic structure in Central Argentina, using biparental markers and comparing the results with those previously obtained by us with mitochondrial DNA (mtDNA) in the same samples. A total of 521 healthy unrelated individuals living in 13 villages of the Córdoba and San Luis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
2
9
1
4
Order By: Relevance
“…The PCA shows, as expected, that Argentinean individuals have different proportions of European, Native American and, much less represented, African ancestry ( S1A Fig ). This pattern, which has already been documented in other admixed populations in South America [33, 45], including in Argentina [1417,34] supports the heterogeneous genetic origins throughout the country. The third and the fifth principal components discriminate three different main Native American ancestries that are also represented in the Argentinean samples.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The PCA shows, as expected, that Argentinean individuals have different proportions of European, Native American and, much less represented, African ancestry ( S1A Fig ). This pattern, which has already been documented in other admixed populations in South America [33, 45], including in Argentina [1417,34] supports the heterogeneous genetic origins throughout the country. The third and the fifth principal components discriminate three different main Native American ancestries that are also represented in the Argentinean samples.…”
Section: Resultssupporting
confidence: 80%
“…The first systematic investigation of human genetic variation in the country focused on a limited number markers either uniparental (mtDNA, Y-STRs, Y-SNP; [2–11] or autosomal (Short Tandem Repeats, Ancestry Informative Markers, Alu sequences, indels, and blood groups [12–17]). Studies based on autosomal markers identified an important inter-individual heterogeneity for the African, Native American and European genetic ancestry proportions [12–17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudios previos muestran que existen importantes diferencias regionales, dadas tanto por las cantidades relativas de cada componente como por la intensidad y dirección del proceso de mestizaje (Avena et al 2012;Corach et al 2010;García et al 2011, entre otros).…”
Section: Introductionunclassified